Optimalisasi Pengelolaan Badan Usaha Milik Desa (Bumdes) dalam Mewujudkan Desa Kreatif di Desa Pademawu Timur Pamekasan - Indien Winarwati; Achmad Syarifudi; Moh Karim; Tri Pujiati; Achmad Badarus Syamsi (Santri : Journal of Student Engagement, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) focuses on strengthening the regulatory framework and management capacity of Village-Owned Enterprises (BUMDes) as a strategic instrument for local economic development. The program aims to optimize BUMDes management in fostering a creative, tourism-based village in Pademawu Timur Village, Pamekasan Regency. The main challenges faced by the community partner include limited understanding among BUMDes managers and village stakeholders regarding the roles, governance mechanisms, and regulatory foundations of BUMDes in supporting social services and sustainable village economic development. The program employed a participatory and sustainable community development approach involving 28 participants, consisting of BUMDes managers, village officials, local MSME actors, and community representatives. The activities were implemented through three sequential stages: (1) socialization of BUMDes roles and regulatory frameworks; (2) educational sessions on BUMDes governance, collaborative governance, and the entrepreneurial ecosystem; and (3) training and mentoring on optimizing BUMDes management through the integration of village tourism potential and local MSMEs. The results indicate a significant improvement in participants’ awareness and understanding of BUMDes as a village economic institution oriented not only toward profit generation but also toward community empowerment, professional governance, and business sustainability. This program is expected to strengthen BUMDes institutional capacity, promote the development of competitive village-based tourism, and contribute to inclusive and sustainable improvements in community welfare and the local village economy.